Peach Cultivar Presivac-1 - Martínez-Calvo, José; Badenes, María L. (ASHS, 2020)
Peach (Prunus persica L. Batsch) is the primary stone fruit grown in Spain. The area devoted to this crop has increased over the past 20 years. Spain ranks third in world production after China and Italy, producing 30% of the total peach crop in the European Union. The diversity in climate of the peach production regions in Spain allows an unusually long peach season, from late April to early November. The chill hours in the peach production areas range from 200 to 400 in the south (Andalucía) to more than 1000 in inland northeast regions (Aragón and Cataluña). Current production is distributed among melting peach cultivars, nectarines, and nonmelting cultivars. Traditional and autochthonous cultivars in Spain are mostly nonmelting peaches. The aroma and quality of the nonmelting cultivars from the Mediterranean basin are very interesting. These nonmelting cultivars are grown in Spain and Italy either for fresh market or for the canning industry. However, these cultivars ripen during the mid or late season; no early cultivars with these characteristics are available in the native peach populations. The program of the Instituto Valenciano de Investigaciones Agrarias (IVIA) and Agromillora Iberia initiated several crosses between nonmelting cultivars that combined the quality of native varieties from the Mediterranean region and earliness of foreign cultivars. One selection from these crosses is the cultivar Presivac-1. ‘Presivac-1’ is an early-ripening peach cultivar with low-to-medium chilling requirements, good agronomic characteristics, very good productivity, and good fruit quality at its time of ripening. The cultivar has the characteristics of a nonmelting peach similar to ‘Jonia’ or ‘Egea’, but it ripens 1 month earlier. ‘Presivac-1’ is also well-adapted to the warm winters and dry summers of the Mediterranean area.